Effect Of Kepok Banana Peel (Musa Paradisiaca L.) Liquid Based Organic Fertilizer On The Growth And Production Of Kale (Brasicca Oleraceae Var. Acephala) Green Dwarf Curly - Widya Eka Aprianti; Rista Delyani; Sigit Normagiat (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to determine the effect of the best POC dose of banana peel on the growth and production of kale plants (Brasicca oleraceae var. acephala) green dwarf curly. This research was conducted at Jalan Perdana gang Wak Sidik Pontianak from November 2020 to March 2021. The research design used was a Complete Randomized Design (RAL) using a single factor, namely the POC dose of banana peel with 5 treatments, namely doses of 0 ml, 10 ml, 20 ml, 30 ml and 40 ml. and repeated 5 times so that there are 25 experimental units. One experimental unit had 5 sample plants so that in this study 125 plants were needed. The observed variables are plant height, number of leaves, stem diameter, wet weight and dry weight. The data were analyzed and continued with the DMRT TEST at a level of 5%. The results showed that the application of liquid organic fertilizer of banana peel kepok with a concentration of 30 ml / polybag had the best influence on plant height, number of leaves, stem diameter and wet weight of kale plants.